Principles of SOPs and hierarchy of documents - Brown, Laura (Henry Stewart Talks, 2013)
What are SOPs?, SOPs ICH, How to write SOPs, Why are SOPs important?, Most common difficulties involved with SOPs, Difference between SOPs and guidelines, SOPs in large companies, Working documents, When and why are SOPs needed?, SOP principles on format and layout of SOPs, SOP control